Answer:
<em>(x - 2)^2 + (y + 1)^2 = 26</em>
Step-by-step explanation:
A circle with center O(2, -1) that passes through the point A(3, 4).
=> The radius of this circle is OA which could be calculated by:
OA = sqrt[(3 - 2)^2 + (4 - (-1))^2] = sqrt[1^2 + 5^2] = sqrt[26]
The equation of a circle with center O(a, b) and radius r could be written as:
(x - a)^2 + (y - b)^2 = r^2
=> The equation of circle O above with center O(2, -1) and radius = sqrt(26) is shown as:
(x - 2)^2 + (y - (-1))^2 = (sqrt(26))^2
<=>(x - 2)^2 + (y + 1)^2 = 26
Hope this helps!
Answer:
Step-by-step explanation:
Use substitution, y=3x+18 so -12x+4(3x+18)=-24. From here you can try to solve for x
-12x+12x+72=-24
The xs cancel, which leaves you with 72=-24
Since 72 cannot equal -24 there is no answer to this system of equations
The answer is A.y32 because you need to multiple
Technically, it would be $.34
Answer:
1625/1
Step-by-step explanation:
put over 1 since it is a whole number